Solving an Old Dogma: Is it an Arteriole or a Venule? - MacGregor Sharp, Matthew; Criswell, Theodore P.; Dobson, Howard; Finucane, Ciara; Verma, Ajay; Carare, Roxana O. (Frontiers in Aging Neuroscience, 2019)
There are very few reliable methods in the literature to discern with certainty between cerebral arterioles and venules. Smooth muscle cells and pericytes are present in both arterioles and venules, so immunocytochemistry for markers specific to intramural cells is unreliable. This study employed transmission electron microscopy and a canine brain to produce robust criteria for the correct identification of cerebral arterioles and venules based on lumen:vessel wall area, tested against the less accurate lumen diameter:vessel wall thickness. We first used morphology of intramural cells to identify two distinct groups of vessels; group 1 with morphology akin to venules and group 2 with morphology akin to arterioles. We then quantitatively assessed these vessels for lumen:vessel wall area ratio and lumen diameter:wall thickness ratio. After assessing 112 vessels, we show two distinct groups of vessels that can be separated using lumen:vessel wall area (group 1, 1.89 -10.96 vs. group 2, 0.27-1.57 (p<0.001) but not using lumen diameter:vessel wall thickness where a substantial overlap in ranges between groups occurred (group 1, 1.58 to 22.66 vs. group 2, 1.40 to 11.63). We therefore conclude that lumen:vessel wall area is a more sensitive and preferred method for distinguishing cerebral arterioles from venules. The significance of this study is wide, as cerebral small vessel disease is a key feature of vascular dementia and understanding the pathogenesis relies in correct identification of vessels.